Reassessing Rights Beyond the Human Species: The Ethics of Inclusion - Metuonu, Iheanacho Chukwuemeka (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
This study investigates the fundamental question: Who really are to be accorded rights—humans or nonhuman animals? Against the backdrop of ethical, legal, and philosophical traditions, the study critically analyzes the ontological basis of moral rights and examines whether nonhuman animals possess the requisite attributes to qualify as right-holders. Drawing on conceptual analysis and philosophical critique, the study evaluates various traditional criteria proposed for ascribing moral rights—including species membership, personhood, rationality, language, and divine endowment—and exposes their insufficiencies in providing an inclusive and defensible justification for rights attribution. The research adopts a normative and analytic methodology rooted in moral philosophy and deontological ethics, particularly the subject-of-a-life criterion as articulated by Tom Regan. This criterion posits that moral rights are due to beings who possess conscious experiences, preferences, emotions, memory, and a sense of future. The study extends this analysis to nonhuman animals, drawing from empirical evidence, common language, behavioural patterns, anatomical similarities, and evolutionary continuities. Findings reveal that many nonhuman animals possess the attributes necessary for moral considerability and that denying them rights on the basis of species alone constitutes unjustifiable speciesism. The significance of this research lies in its robust philosophical foundation for extending moral rights beyond human boundaries. Ultimately, this study calls for an expansion of moral rights beyond the human sphere, proposing a more inclusive ethical framework grounded in respect for all sentient beings.